Strategy Of Translating Gadget Brochure - Deny Kusuma (RETORIKA: Jurnal Ilmu Bahasa, 2015)
The title of this writing is strategy of translating gadget brochure. There were two problems discussed in this thesis, namely (1) terms found in the gadget manual book and its equivalence in Indonesia, (2) strategies applied in translating gadget brochure. Based on the analysis result, it was found that the terms and its equivalent words found in the gadget brochure were classified based on: 1) simple words or compound words and terminology forming phrase. 2) words category found are: noun and verb. The recommended pattern to determine the equivalent word was pure borrowing strategy, not Â adaptation borrowing strategy. The adaptation borrowing in this context was related to the spellings, the pronunciation or sound adaptation in the TL rather than adaptation for the cultural substitutes that conceptually mismatches with the standardized terminology in the SL. In addition, the result of the analysis that there were seven strategies found in gadget brochure, they were translation by more general word (Superordinate), translation by a more neutral/expressive word, translation by cultural substitution, translation by using loan word or loan word plus explanation, translation by paraphrase using related word, translation by omission and translation by illustration.Â Keywords: Gadget brochure, Strategies of translation